Economics of Nature Based Solutions (NBS) Meta-analysis: R-Project - Steward, Peter Richard; Rosenstock, Todd S.; Joshi, Namita; Magnan, Nicholas; Ombewa, Babra Vivian Adhiambo; Mumo, Elijah Mustoki; Kacha, Gabrielle Nour; Muller, Lolita; Youngberg, Brayden (2023)
An R project to compile and analyse an excel based meta-dataset of nature based solution outcomes.